GAC to BAC: Does it make chloraminated drinking water safer?. (1st April 2020) - Cuthbertson, Amy A.; Kimura, Susana Y.; Liberatore, Hannah K.; Knappe, Detlef R.U.; Stanford, Benjamin; Summers, R. Scott; Dickenson, Eric R.; Maness, J. Clark; Glover, Caitlin; Selbes, Meric; Richardson, Susan D.
Abstract: Biological activated carbon (BAC) is widely used as a polishing step at full-scale drinking water plants to remove taste and odor compounds and assimilable organic carbon. BAC, especially with pre-ozonation, has been previously studied to control regulated disinfection by-products (DBPs) and DBP precursors. However, most previous studies only include regulated or a limited number of unregulated DBPs. This study explored two full-scale drinking water plants that use pre-chloramination followed by BAC and chloramine as the final disinfectant. While chloramine generally produces lower concentrations of regulated DBPs, it may form increased levels of unregulated nitrogenous and iodinated DBPs. We evaluated 71 DBPs from ten DBP classes including haloacetonitriles, haloacetamides, halonitromethanes, haloacetaldehydes, haloketones, iodinated acetic acids, iodinated trihalomethanes, nitrosamines, trihalomethanes, and haloacetic acids, along with speciated total organic halogen (total organic chlorine, bromine and iodine) across six different BAC filters of increasing age. Most preformed DBPs were well removed by BAC with different ages (i.e., operation times). However, some preformed DBPs were poorly removed or increased following treatment with BAC, including chloroacetaldehyde, dichloronitromethane, bromodichloronitromethane, N -nitrosodimethylamine, dibromochloromethane, tribromomethane, dibromochloroacetic acid, and tribromoacetic acid. Some compounds, including dibromoacetaldehyde, bromochloroacetamide, and dibromoacetamide, were formed only after treatment with BAC. Total organic halogen removal was variable in both plants and increases in TOCl or TOI were observable on one occasion at each plant. While calculated genotoxicity decreased in all filters, decreases in overall DBP formation did not correlate with decreases in calculated cytotoxicity. In three of the six filters, calculated toxicity increased by 4–27%. These results highlight that DBP concentration alone may not always provide an adequate basis for risk assessment. Graphical abstract: Image 1 Highlights: Most of the preformed unregulated DBPs analyzed in this study can be removed by biodegradation. BAC reduced regulated and unregulated DBP concentrations (preformed and SDS). Some DBPs increased following BAC (CAL, DCNM, BDCNM, NDMA, DBCM, TBNM, DBCAA, and TBAA). Lower DBP concentrations in BAC effluents did not always correlate to lower calculated cytotoxicity. BAC showed promising reductions in calculated genotoxicity.